AKTIVITAS ENZIM PELARUT FOSFAT DAN EFEKTIVITAS MIKROBA ASAL WAMENA UNTUK MENUNJANG PERTANIAN RAMAH LINGKUNGAN PADA DAERAH MARGINAL - Sri Widawati (Jurnal Teknologi Lingkungan, 2010)
The activity of phosphate solubilizing enzyme and the effectivity of microbe from Wamena for support agriculture of environmental friendliness at marginal area. Phosphate dissolution of enzyme by microbial effective in compost plus from Wamena forest was stored in the freezer for 4 years, have been conducted in Ecofisiology laboratory,Microbiology devision, Research Center for Biology, Indonesian Institute of Science. This research was conducted to know the microbial affectivity and the activity of phosphate solubilizing enzyme of 20 microorganisms in inoculants stored 4 years in refrigerated room and to support soil fertility and biofertilizer agent in organic farming system. This research used plate count methode for counting the amount of microbial population, Scinner method was used toanalizer enzyme of alkaline and acid PME-ase,and statistical analysis use Duncan methode. The storage of 20 inoculants invected 20microorganisms for 4 years in refrigerated room showed that the microbial activity still high with the amount of mean population 107 and the activity of phosphate solubilizing enzyme with mean diameter of clear zone (holozone) 1 cm – 2 cm. The effectivity and the highest activity of phosphate solubilizing enzyme were : Azotobacter indicus (A), Bacillus panthothenticus (D), Bacillus megaterium (M), Bacillus thuringiensis (O), Ceratia sp. (R),Chromobacterium lividum (G), Chromobacterium violaceum (S), Flavobacterium breve(T), Klebsiella aerogenes (H), Pseudomonas fluorescent (J), Rhizobium legurxinosarium (L), and the lowest were: Streptomyces sp. (I) .Key word: Alkaline and acid PMEase, Phosphate solubilizing bacteria,Biofertolizer